2022
DOI: 10.1101/2022.10.21.22281346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decoding the endometrial niche of Asherman’s Syndrome at single-cell resolution

Abstract: Asherman’s Syndrome (AS) is characterized by intrauterine adhesions, which cause infertility, menstrual abnormalities, and recurrent pregnancy loss. While AS occurs as a consequence of traumatic or infectious disruption of the endometrial cell niche, its pathophysiology remains largely unknown and treatment strategies have been restricted to recurrent hysteroscopic removal of intrauterine adhesions with limited success.We decoded the disrupted endometrial cell niche associated with AS at single-cell (sc) resol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 73 publications
0
0
0
Order By: Relevance
“…Studies have revealed a reduction in the signaling interactions within the Notch pathway, specifically involving JAG1-Notch2, within the glandular, glandular secretory and luminal epithelial cells. This alteration correlates with the disrupted process of differentiation within the glandular epithelium in AS that can affect fertility and reproductive health [53].…”
Section: Notch Signaling: a Key Driver In The Pathogenesis Of Asherma...mentioning
confidence: 97%
See 2 more Smart Citations
“…Studies have revealed a reduction in the signaling interactions within the Notch pathway, specifically involving JAG1-Notch2, within the glandular, glandular secretory and luminal epithelial cells. This alteration correlates with the disrupted process of differentiation within the glandular epithelium in AS that can affect fertility and reproductive health [53].…”
Section: Notch Signaling: a Key Driver In The Pathogenesis Of Asherma...mentioning
confidence: 97%
“…It can be anticipated that variations in the Notch pathway gene expression profiles can serve as prediction markers for the onset or progression of illnesses, offering clinicians significant tools for early identification and prognostic evaluation. The following details attempt to explore how Notch signaling may be involved in specific gynecological diseases (Figure 3): [50], adenomyosis [51], pre-eclampsia [52], PCOS (Polycystic ovarian syndrome) [50], Asherman's syndrome [53], infertility [54], and POI (primary ovarian insufficiency) [55] relative to healthy controls. It also unveils the captivating influence of Notch signaling in shaping the intricate processes of implantation and decidualization during pregnancy.…”
Section: Unlocking the Notch: Exploring Its Impact On Reproductive Di...mentioning
confidence: 99%
See 1 more Smart Citation
“…Modern single-cell transcriptomic approaches offer additional opportunities to construct an unbiased portrait of nonregenerative healing in the uterus. For example, recent work compared single-cell expression profiles from a human endometrium atlas to those from patients with moderate and severe AS (Santamaria et al 2022, Wang et al 2020). This study reported profound changes in the composition and function of AS uteri, including unique epithelial and smooth muscle cell populations, a proinflammatory immune cell state, fibrotic stroma, and compromised vascularity.…”
Section: Mechanisms Of Uterine Fibrosismentioning
confidence: 99%
“…This improvement likely occurs through the modulation of the uterine niche, as opposed to substantial cellular repopulation, as human CD133 + BMDSCs transplanted into the same AS mouse model engraft around endometrial vessels and promote glandular epithelial proliferation (Cervelló et al 2015). BMDSC-based approaches have since been translated to phase I/II clinical trials for the treatment of AS and endometrial atrophy, and shown to partially reverse AS-associated transcriptional signatures following treatment (Santamaria et al 2016(Santamaria et al , 2022. A variety of other cell-based therapies have been explored in similar models, including MSCs from adipose tissue, umbilical cord, or amniotic membranes (Gan et al 2017, Kilic et al 2014, Tang et al 2016; uterine-or menstrual blood-derived cells (Hu et al 2019, Liu et al 2018; and human embryonic stem cell-derived endometrium-like cells (Song et al 2015).…”
Section: Therapeutic Management Of Uterine Fibrosismentioning
confidence: 99%